2014
DOI: 10.3762/bjoc.10.161
|View full text |Cite
|
Sign up to set email alerts
|

C–H-Functionalization logic guides the synthesis of a carbacyclopamine analog

Abstract: SummaryThe chemical synthesis of carbacyclopamine analog 2, a cyclopamine analog with an all-carbon E-ring, is reported. The use of C–H-functionalization logic and further metal-catalyzed transformations allows for a concise entry to this new class of acid-stable cyclopamine analogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…This has subsequently been exploited in several impressive syntheses. 1921 As part of a natural product synthesis effort, the Baran group reinvestigated this interesting oxidation after a vast exploration of alternative methods and strategies failed. The reaction conditions were subsequently improved (ascorbic acid as reductant, shorter reaction times, and higher yields) and applied to the first synthesis of highly oxygenated polyoxypregnane steroids with useful biological properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has subsequently been exploited in several impressive syntheses. 1921 As part of a natural product synthesis effort, the Baran group reinvestigated this interesting oxidation after a vast exploration of alternative methods and strategies failed. The reaction conditions were subsequently improved (ascorbic acid as reductant, shorter reaction times, and higher yields) and applied to the first synthesis of highly oxygenated polyoxypregnane steroids with useful biological properties.…”
Section: Introductionmentioning
confidence: 99%
“… Derivatization of the C17 ketone of steroid substrates to generate a bidentate imino-pyridine ligand combined with the addition of a Cu I source (or Cu II + reductant) and dioxygen led to the selective hydroxylation of C12 with modest yields (up to 50%). This has subsequently been exploited in several impressive syntheses. As part of a natural product synthesis effort, the Baran group reinvestigated this interesting oxidation after a vast exploration of alternative methods and strategies failed. The reaction conditions were subsequently improved (ascorbic acid as reductant, shorter reaction times, and higher yields) and applied to the first synthesis of highly oxygenated polyoxypregnane steroids with useful biological properties .…”
Section: Introductionmentioning
confidence: 99%
“…During this work the problem of reversing the endo/exo selectivity of the Wagner-Meerwein rearrangement was addressed effectively via applying Comins' reagent (20) and excess DMAP and using toluene as the solvent. 15 In fact the reaction course was shifted in favor of the desired endocyclic isomer reaching to an almost quantitative yield with the impressive ratio of 3.3:1 (endo/exo isomer) instead of 3:7 in previous approaches (Scheme 5).…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…To overcome the acid lability of cyclopamine and to gain more insight into structure-activity relationships, cyclopamine analogue 29 was synthesized. 20 In this derivative the oxygen atom in ring E was replaced by a CH moiety. The retrosynthetic analysis is outlined in Scheme 9.…”
Section: Synthesis Of a Carbacyclopamine Analoguementioning
confidence: 99%
“…Through utilization of a late-stage functionalization of cyclopamine, a kilogram-scale approach to the synthesis of saridegib has been developed . In addition to these exciting developments, it has been shown that introducing structural modifications to the parent structure of cyclopamine can allow increased stability as well as improved Hh signal inhibition . With these possibilities in mind, a de novo synthesis is attractive as it might allow modifications in different regions of the parent structure and potentially provide a more diverse array of analogues.…”
mentioning
confidence: 99%